Functions of legal responsibility in private law: selected isues - Зелена, Ірина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article reveals the essential features and functions are formulated definition of legal responsibility in private law. To this end, research was conducted scientific understanding of the functions of the positions of legal responsibility and disclosed the structure of the legal liability in private law. Proposed function of legal responsibility in private law regarded as areas of legal exposure segregated system of legal rules on uniform, the individual social relations of a private nature, which are manifested in the establishment of certain legal boundaries of behavior of a person to the right.